"It Is Likely a White Gene": Racial Voyeurism and Consumption of Black Mothers and "White" Babies in Online News Media. Issue 1 (February 2020) - Moss, Sonita R.; Roberts, Dorothy E.
Focusing on media reports of black women who give birth to "white" children, this study asks: What can we learn about popular understandings of race from the fascination with births of "white" babies born to black mothers? What racial discourses guide how such stories are produced and consumed online? We conducted a critical discourse analysis of media coverage and online comments about two contemporary cases. We found that three race-based assumptions underlie and are reinforced by these narratives. We argue that these births generate racial voyeurism because they violate deeply held beliefs about racial identity and the reproduction of race.